Assessment of Existing Green Building Implementation in Government Buildings toward Energy Efficiency - Guntaryono Guntaryono; Darmansjah Tjahja Prakasa; Andarita Rolalisasi; Nur Azizah Affandy (Transpublika Publisher, 2025)
Government buildings represent a major portion of public-sector energy consumption and contribute substantially to greenhouse gas emissions due to intensive cooling, lighting, and suboptimal building envelopes. In many developing countries, including Indonesia, the majority of government facilities were constructed prior to the adoption of green building regulations, resulting in poor energy performance and elevated operational costs. This study aims to critically assess the energy performance of an existing government building and to identify practical retrofit strategies based on Green Building principles that can support national carbon reduction commitments and Sustainable Development Goals. A mixed-methods case study was conducted on the East Java Public Works and Human Settlements Office Building (6,000 m²; three stories; pre-regulation construction). Data collection combined field inspection, structured interviews with facility managers, and policy-document review. The evaluation proceeded through four stages: calculation of Energy Use Intensity (EUI), disaggregation of energy consumption by end-use, performance assessment of the building envelope, ventilation, and lighting, and compliance analysis against national standards, Greenship GBCI criteria, and relevant SDG targets. The results indicate that cooling, lighting, and deficiencies in the building envelope account for the largest share of total energy consumption. Consequently, the most effective retrofit strategies involve improving the thermal performance and insulation of the building envelope, replacing conventional lighting with energy-efficient systems, and optimizing HVAC operations through equipment upgrades and better control management. This study provides an evidence-based framework to guide public retrofit policies and contributes valuable empirical insights to the broader discourse on energy efficiency in government buildings.